2008
DOI: 10.1111/j.1349-7006.2008.00904.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of peroxisome proliferator‐activated receptor γ activity suppresses pancreatic cancer cell motility

Abstract: Peroxisome proliferator-activated receptor g (PPARg) is a ligandactivated transcription factor that has been implicated in the carcinogenesis and progression of various solid tumors, including pancreatic carcinomas. We aimed to clarify the role of this receptor in pancreatic cell motility in vitro and in metastasis in vivo. P ancreatic ductal adenocarcinoma is associated with one of the highest mortality rates in patients with malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 30 publications
4
28
0
Order By: Relevance
“…Moreover, we noted higher PPAR-γ expression in GBM cells, which could contribute to their rapid proliferation. Consistent with this, a previous study found that PPAR-γ activation induced tumor formation and reduced the overall survival time in pancreatic cancer (32). GBM cells have highlevel of LDH as glycolytic enzyme and SDH as enzyme for TCA cycle compared to NB cells.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, we noted higher PPAR-γ expression in GBM cells, which could contribute to their rapid proliferation. Consistent with this, a previous study found that PPAR-γ activation induced tumor formation and reduced the overall survival time in pancreatic cancer (32). GBM cells have highlevel of LDH as glycolytic enzyme and SDH as enzyme for TCA cycle compared to NB cells.…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, we posited that MKK4 functions as a tumor suppressor in lung adenocarcinomas driven by mutant Kras and Tp53 and tested this hypothesis in mice. The findings reported here support this hypothesis and revealed that MKK4 functions as a tumor suppressor partly by decreasing levels of peroxisomal proliferatoractivated receptor ␥ (PPAR␥), a nuclear receptor for fatty acids and eicosanoids that plays divergent roles in different tumor models (31,32,37,41,42). S-Label; MP Biomedicals) for 45 min.…”
Section: Figsupporting
confidence: 68%
“…7B). One of the genes with the most prominently increased (5.0-fold) expression was PPAR␥, a transcription factor that functions as a nuclear receptor for fatty acids and eicosanoids and can reportedly promote or inhibit tumorigenesis (31,32,37,41,42). Pparg encodes two protein isoforms (␥1 and ␥2), the mRNA levels of which increased 1.5-and 6.3-fold, respectively, following MKK4 knockdown in 393P cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PPAR-c is a nuclear receptor serving as a transcription factor to control cell differentiation, apoptosis and glucose metabolism (Kliewer and Wilson 1998). Ligands for PPAR-c such as anti-diabetic drugs of the thiazolidinedione (TDD) class pioglitazone, troglitazone and rosiglitazone (Cho and Momose 2008;Krentz et al 2008) exert anti-inflammatory effects and reduce PC growth in experimental models (Nakajima et al 2008;Dong et al 2009). The antiinflammatory effects associate with suppression of COX-2 and NF-jB activities, evidencing complex intracellular pathways and their suppression of tumor growth partially occurs via reducing VEGF (Dong et al 2009).…”
Section: Ppar-c Ligands: General and Pancreas Cancer-specific Anti-tumentioning
confidence: 98%